Photovoltaics: Reduced Graphene Oxide Micromesh Electrodes for Large Area, Flexible, Organic Photovoltaic Devices (Adv. Funct. Mater. 15/2015). (April 2015) - Konios, Dimitrios; Petridis, Constantinos; Kakavelakis, George; Sygletou, Maria; Savva, Kyriaki; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : A facile, one step, roll‐to‐roll compatible laser patterning technique to improve and simultaneously tune the optoelectronic properties of graphene based transparent conductive electrodes (TCE) is demonstrated by E. Stratakis, E. Kymakis, and colleagues on page 2213. In order to overcome the trade‐off between the sheet resistance and transparency, reduced graphene oxide micromeshes are laser‐patterned on plastic substrate and incorporated in flexible organic photovoltaic devices as the TCE.